2008
DOI: 10.4049/jimmunol.181.7.4676
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for CD4+ T Cells in the Control of Cachexia

Abstract: Cachexia is the dramatic weight loss and muscle atrophy seen in chronic disease states, including autoimmunity, cancer, and infection, and is often associated with lymphopenia. We have previously shown that CD4+ T cells that express the lowest density of CD44 (CD4+CD44v.low) are significantly reduced in diabetic NOD mice that are cachexic compared with diabetic mice that are not cachexic. Using this model, and a model of cancer cachexia, we test the hypothesis that CD4+CD44v.low cells play an active role in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 74 publications
1
33
0
1
Order By: Relevance
“…Interaction among these factors is not well known. However, a recent report indicates that certain CD4 + T cells might protect against tumor-induced cachexia [40]. We previously found that chronic alcohol consumption in mice bearing subcutaneous B16BL6 melanoma leads to a major loss in body fat which is reflected in a twofold increase in body weight loss at necropsy compared to melanoma-bearing mice drinking water [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction among these factors is not well known. However, a recent report indicates that certain CD4 + T cells might protect against tumor-induced cachexia [40]. We previously found that chronic alcohol consumption in mice bearing subcutaneous B16BL6 melanoma leads to a major loss in body fat which is reflected in a twofold increase in body weight loss at necropsy compared to melanoma-bearing mice drinking water [22].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 int and CD44 v.low cells are equivalent in their ability to generate Th1-type responses. Whether the pro-Th2-type cytokine environment generated by CD44 v.low cells plays a role in their capacity to inhibit cancer cachexia, a syndrome that is strongly associated with inflammation [25] remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CD44 v.low cells give rise to a large clonally diverse pool with a balanced ratio of naïve and memory cells, and a non-inflammatory cytokine profile. A functional difference between these two cell subsets is further highlighted by the ability of CD44 v.low cells, but not CD44 int cells, to inhibit both diabetes and cancer associated cachexia [25]. …”
Section: Discussionmentioning
confidence: 99%
“…CD4 þ T cells that express the lowest density of CD44 (CD4 þ /CD44 very low ) are significantly reduced in cachectic diabetic NOD mice in comparison to noncachectic mice. Wang et al [28] demonstrated that CD4 þ /CD44 very low cells delay the onset of cachexia when infused into recipient mice and, moreover, they significantly reduce muscle atrophy and inhibit muscle protein loss and DNA loss, even when given after the onset of cachexia. Protection from wasting and muscle atrophy by CD4 þ /CD44 very low cells is associated with protection from lymphopenia [28].…”
Section: Cd4 R T Cellsmentioning
confidence: 98%